Full-spectrum cannabis extracts for women with chronic pain syndromes: a real-life retrospective report of multi-symptomatic benefits after treatment with individually tailored dosage schemes - Soares Silva, Patrícia Montagner; Medeiros, Wesley; Nogueira Borges, Clarissa; Brasil-Neto, Joaquim P.; Lessa Jr., Wilson; Ferreira de Oliveira e Silva, Ricardo; Caixeta, Fabio V.; Malcher-Lopes, Renato (Frontiers in Pharmacology, 2025)
Chronic pain syndromes (CPS) are debilitating conditions for which cannabis extracts and cannabinoids have shown promise as effective treatments. However, accessibility to these treatments is limited due to the absence of suitable formulations and standardized dosage guidelines. This is particularly critical for women, who present sex-specific differences in pain burden, pain perception, and pain-related cannabinoid pharmacology. We conducted a retrospective open-label cross-sectional study on 29 female CPS patients who received full-spectrum cannabis extracts (FCEs) with standardized compositions produced by two patient-led civil societies. An individually tailored dosage protocol was used, with dosage schemes adjusted based on individualized clinical assessments of initial conditions and treatment responses. Patients received either CBD-dominant extracts, THC-dominant extracts, or a combination of both. To evaluate the results, we conducted a comprehensive online patient-reported outcome survey covering core CPS symptoms, comorbidities, personal burden, and quality of life—including open-ended questions to capture the practical and subjective impacts of CPS and FCEs treatment on patients’ lives. Despite most patients already using medications for pain and mood disorders, all reported some level of pain relief, and most reported improvements in cognitive function, motor abilities, professional activities, irritability, anxiety, melancholy, fatigue, and sleep quality. Qualitative content analysis of open-ended responses revealed that FCEs had relevant positive effects on practical and subjective domains, as well as personal relationships. No patients had to discontinue extract use due to adverse effects, and most reduced or ceased their use of analgesic and psychiatric medications. The optimal dosage regime, including CBD-to-THC proportions, was established through a response-based protocol, varied considerably, and showed no clear link to specific pain types. These real-life results strongly suggest that a broad scope of benefits can be achieved by using flexible dosing schemes of cannabis extracts in managing diverse CPS conditions in female patients. Therefore, this study highlights the significance of tailoring treatment plans to individual CPS cases. Moreover, it demonstrates the feasibility of utilizing quality-controlled cannabis extracts produced by civil societies as either adjuncts or primary pharmacotherapeutic options in CPS management.